The association between serum magnesium and chronic kidney disease in Chinese adults: a cross-sectional study - Xie, Jing-Zhi; Huang, Yuanyuan; Zheng, Xiao-Feng; Feng, Ruimei; Li, Xiao-Yun; Zheng, Zi-Gui; Jiang, Bing-Jing; Du, Shanshan; Chen, Heng-Gui; Xu, Yanfang (BMC public health, 2024)
Background Magnesium (Mg) is both an essential macro-element and a known catalyst, and it plays a vital role in various physiological activities and mechanisms in relation to chronic kidney disease (CKD). However, epidemiological evidence involving this is limited and not entirely consistent. This study aims to explore the association of serum Mg concentrations with the risk of CKD among general Chinese adults. Methods A total of 8,277 Chinese adults were included in the wave of 2009 from the China Health and Nutrition Survey (CHNS). The primary outcome was the risk of CKD, which was defined as the estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73 m 2 . Multivariable logistic regression model was used to examine the relationship of serum Mg concentrations with the risk of CKD. Results Included were 8,277 individuals, with an overall CKD prevalence of 11.8% ( n = 977). Compared with the first quartile of serum Mg, the multivariable-adjusted odds ratios (ORs) and 95% confidence intervals (CIs) for participants in the second, third, and fourth quartiles of serum Mg were 0.74 (0.58, 0.93), 0.87 (0.69, 1.11) and 1.29 (1.03, 1.61), respectively. Similar results were observed in our several sensitivity analyses. Restricted cubic spline analysis demonstrated a nonlinear (similar “J”-shaped) association between serum Mg concentrations and the risk of CKD ( P nonlinearity <0.001), with a threshold at around a serum Mg value of 2.2 mg/dL. Conclusions Our results suggested a similar “J”-shaped association between serum Mg concentration and the risk of CKD among Chinese adults. Further large prospective studies are needed to verify these findings.